Non-intuitive clustering of 9,10-phenanthrenequinone on Au(111) - Brown, Ryan D.; Quardokus, Rebecca C.; Wasio, Natalie A.; Petersen, Jacob P.; Silski, Angela M.; Corcelli, Steven A.; Kandel, S. Alex (Beilstein Journal of Nanotechnology, 2017)
The direct injection of a 9,10-phenanthrenequinone in tetrahydrofuran solution on a Au(111) substrate in high vacuum results in the formation of metastable clusters with a non-intuitive structure. Metastable, rectangular tetramers of this molecule form in which the net molecular dipoles all orient toward the center of the cluster. This structure does not allow for additional hydrogen bonding and thus the origin of its metastability is not clear. We compare this feature to other structures observed on this surface, as well as those formed during the deposition of 9-fluorenone, which does not exhibit this anomalous clustering behavior.
Keywords: metastable clusters; 9,10-phenanthrenequinone; scanning tunneling microscopy; self-assembly